Characterization of Cetylpyridinium Bromide-Modified Montmorillonite Incorporated Cellulose Acetate Nanocomposite Films - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (Kluwer Academic Publishers, 2015)
An organoclay (MMT–CPB) based on montmorillonite (MMT) and cetylpyridinium bromide (CPB) was synthesized by a cationic interchange process. The presence of CPB into the clay structure was evidenced by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA). This organoclay was then used to prepare cellulose acetate (CA) nanocomposite films with different content of this nanofiller (2.5–7.5 wt%) through a casting technique. All nanocomposites were characterized by XRD, FTIR, differential scanning calorimetry, TGA, optical and mechanical analyses. So, nanocomposites were characterized by the intercalation of CA into the clay structure. Organoclay content did not affect the glass transition (Tg) and melting temperature (Tm) of CA; however, thermal stability of CA was slightly improved with the presence of the organoclay. Therefore, optical and mechanical properties were significantly affected with the increase of the organoclay content into the CA. On the other hand, electrical conductivity (EC) measurement was performed to evaluate the release of cetylpyridinium from the CA nanocomposites to an aqueous medium. An important increase of the EC over time was observed. Therefore, the EC values were dependent on the content of MMT–CPB in the CA nanocomposites. However, a likely degradation of cellulose acetate in the aqueous medium affected the surfactant quantification. © 2015, Springer Science+Business Media New York.